(untitled) (Praxis Educativa, 2025)
This article is based on a study developed in Iquique that describes and analyzes the implementation of the tutoring program of the School Reactivation plan promoted by the Ministry of education in Chile with the aim of improving school attendance, learning, coexistence, and mental health conditions in chilean schools affected by the suspension of classes during the pandemic caused by the Covid- 19 virus. In this regard the research was based on reconding the experiences of the protagonists, namely, the tutors who where university students of pedagogy careers two municipalized basic education schools in the city of Iquique in the Tarapacá region in the extreme north of Chile. The study is qualitative in nature and was based on in-depth interviews and focus groups with students and the university coordination of the program, revealing the implementation of the program and its effects on the improvement of learning and emotional support, as well as its irregular development in the selected schools.